Case Report: Overcoming challenges in pancreatic cancer with liver metastases: a personalized therapeutic odyssey of TACE, ablation, and immunotherapy - Zhu, Ying; Ning, Zhouyu; Meng, Zhiqiang (Frontiers in Immunology, 2023)
Pancreatic cancer represents a malignant neoplasm originating from pancreatic cells.The optimal approach to cancer treatment remains uncertain, lacking a definitive consensus. Here, we present a compelling case of a 49-year-old female with pancreatic head cancer with liver metastases, as identified by CT and confirmed by biopsy. PET-CT indicated widespread metastatic involvement. TACE therapy with gemcitabine and cisplatin was initiated, yielding a stable disease response. The patient's high PD-L1 expression prompted TACE-PD-1 monoclonal antibody combination therapy.Subsequent treatments, including ablation, sustained PD-1 immunotherapy, and consolidation TACE, culminated in a complete response, as evidenced by imaging and tumor marker dynamics. Our case underscores the potential of multifaceted strategies in managing aggressive pancreatic cancer